2012
DOI: 10.2106/jbjs.j.01822
|View full text |Cite
|
Sign up to set email alerts
|

Lower Extremity-Specific Measures of Disability and Outcomes in Orthopaedic Surgery

Abstract: "Lower extremityspecific measures of disability and outcomes in orthopaedic surgery

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
68
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 95 publications
(68 citation statements)
references
References 109 publications
0
68
0
Order By: Relevance
“…Differences in EQ-5D and HHS must be observed with caution as they did not reach minimal clinically important differences. The EQ-5D has been shown to have a mean minimal clinically important difference in patients having THA of 0.31 [25], while the HHS has minimal clinically important differences of 7 to 9 [32]. There is no established minimal clinically important difference for the UCLA activity score.…”
Section: Discussionmentioning
confidence: 99%
“…Differences in EQ-5D and HHS must be observed with caution as they did not reach minimal clinically important differences. The EQ-5D has been shown to have a mean minimal clinically important difference in patients having THA of 0.31 [25], while the HHS has minimal clinically important differences of 7 to 9 [32]. There is no established minimal clinically important difference for the UCLA activity score.…”
Section: Discussionmentioning
confidence: 99%
“…Although improvements in mean postoperative functional scores were statistically significant as a result of the large number of patients included in this study, these differences are generally smaller than the minimum clinically important differences (MCIDs) that have been reported for THA. Smith et al [31] reported an MCID range for HHS between 7 and 9 points and an MCID for WOMAC physical function subscore as 12% of baseline score or 6% of maximum score (5-6 points). Furthermore, although activity levels may be helpful in defining patients at risk, it is important to note that the majority of failures after THA may not be related to wear.…”
Section: Discussionmentioning
confidence: 99%
“…The study cohort and the total population of younger TKA patients and non-included younger TKA patients were similar with respect to gender (74.1% vs 67.7% female, p = 0.23), mean age (50.1 vs 50.0 years, p = 0.99), and mean BMI (34.2 vs 33.0, p = 0.21). Patients in the study cohort reported higher mean WOMAC physical function scores compared to non-included younger TKA patients (48.1 vs 43.0 points, p = 0.03) and demonstrated a trend towards higher mean WOMAC pain scores (43.3 vs 39.1 points, p = 0.06), although both of these differences are below the minimal clinically important difference (MCID) for these measures (Table 1) [21]. Among the older TKA patients, the study cohort included a higher proportion of female patients (71.4% vs 60.3%, p = 0.06), but there was no difference in mean age, (69.5 vs 69.5 years, p = 0.85) or mean BMI (31.1 vs 32.1 kg/m 2 , p = −0.23).…”
Section: Methodsmentioning
confidence: 96%